From democratic recovery to the risk of breakdown. Peruvian permanent instability (2001-2022) and possible causes - García Marín, Ignacio (2024)
This study analyzes Peru’s political trajectory after the recovery of its democracy in 2001 and until Castillo’s failed self-coup in 2022. Accordingly, it examines the main formal characteristics of its form of government, the main indicators of the party system, and the relationships between powers during the period in question. Thus, this period stands out for growing executive instability, with the permanence of heads of state, premiers, and ministers being increasingly fleeting. Likewise, the Congress was characterized by progressive distancing and hostility, reflected in a notable use of the motion of censure and impeachment, as well as a high level of fragmentation and transfuguism. Apparently, the parliamentary design of Peruvian presidentialism, in combination with its non-existent party system and the low democratic commitment of the main political leaders, would explain the gradual threat to democracy observed in this period.